Outpatient physiotherapists' attitudes and beliefs toward patients with chronic pain: A qualitative study. (2nd January 2020) - Morin Chabane, Sabrina; Coutinho, Franzina; Laliberte, Maude; Feldman, Debbie
ABSTRACT: Purpose : To conduct a knowledge translation exercise by sharing knowledge from a scoping review, describing physiotherapists' attitudes toward and beliefs about chronic pain, and to gain perspectives on these findings from physiotherapists working with this clientele. Method : We conducted three focus groups with a total of 14 outpatient physiotherapists working in public hospitals. We first showed a video (reflecting an encounter between a clinician and a person living with chronic pain) created based on themes that emerged from a scoping review we conducted, followed by a discussion about attitudes and beliefs toward chronic pain. The sessions were audio-taped and transcripts were analyzed through descriptive and thematic analysis. Results : The consultations reinforced three core themes related to physiotherapists' attitudes toward and beliefs about chronic pain: 1) the development of chronic pain; 2) the relationship to disability and the legitimacy of chronic pain; and 3) physiotherapists' ability to manage psychological aspects of their patient's pain. Conclusion : Physiotherapists in our sample appear unsure of how to interpret severe pain within the context of minimal objective findings. Physiotherapists may benefit from training on how to assess and treat psychosocial factors associated with pain.